Physical activity and sitting time prior to and during COVID-19 lockdown in Austrian high-school students - Klaus Greier; Clemens Drenowatz; Theresa Bischofer; Gloria Petrasch; Carla Greier; Armando Cocca; Gerhard Ruedl (AIMS Press, 2021)
The COVID-19 pandemic has led in many countries to the implementation of policies that mandate social distancing and movement restrictions. While these measures are warranted in order to minimize the spread of the virus they may have detrimental effects on various behaviors, including physical activity (PA). The present study examined PA and sitting time in 14 to18-year-old Austrian high school students prior to and during the second COVID-19 lockdown in Austria. Data was collected via an online questionnaire during fall/winter 2020/21. Questions were based on the International Physical Activity Questionnaire, which examined frequency and duration of PA and sitting time. A total of 221 high school students provided valid data. Participants reported significantly lower moderate and vigorous PA during the lockdown while sitting time increased (p < 0.01). The frequency of walking (days/week) also decreased during COVID-19 lockdown, which also contributed to a significant decline in total walking time (p < 0.01). Further, the decline in PA was more pronounced in boys, while girls reported a greater decline in walking. These differences were due to higher PA and walking in boys and girls, respectively, prior to the lockdown. During the lockdown sex differences in PA and sitting time were limited. Taken together, these results highlight the impact of COVID-19 policies on PA in adolescents and emphasize the importance to promote an active lifestyle even in times of home confinement.